ANALISIS PENGAMBILAN KEPUTUSAN RUMAH TANGGA DALAM MEMBELI PRODUK SEMEN ( Studi Pada Rumah Tangga di Kota Surabaya) - Joni - Gunawan; Agung - Yuniarinto; Thantawi AS - - (Wacana Journal of Social and Humanity Studies, 2010)
ABSTRACT An interesting thing necessary to investigate deeply is how should â€œthe cemment productâ€ be positioned and which marketing strategy should be formulated and executed in marketing building material products such as cemment? In line with this explanation, this study analyze the psicological, social, and marketing mixing effects on household decision in buying cemment product. The strategic implication of this is to show the product strategy, price, promotion, and distribution as well as to decide the positioning of the â€œcemment productâ€ which is oriented to the psichological and social variables of the household consumers. The psichological, social, and marketing mixing effects that become the main attentions in this study are the: motivation, attitude, reference group, product, price, promotion and distribution affects. A high individualâ€™s expectation in possesing a proper house makes the individual secrafice all they have to obtain a house. Viewed from business aspects, this case is considered as a market opportunity for products which are able to supply and/or maintain proper houses, especially for cemment product. This indication appears from the quantity of new companies in this field of business both in direct investment or share holding. Consequently, the competition of the product is relatively tight. The position of the cemment product that is strategic for the construction sector and the cemment product as commodity as well as industrial goods need fix strategy to market. This study findings are: consumers of â€œcemment productâ€ in Surabaya are 35 to 50 years old and their major job are business / employee, most of them own relative low buying capability. Household consumers of the â€œcemment productâ€ in Surabaya have relative high education levels. They are Senior High School to University Graduated and most of the consumers are male, and they tend to have rational buying decision. Results of relationship analysis among variables which were obtained at the level of significance 0,05 are show that motivation and atitude are significantly affect household decision in buying â€œcemment productâ€ in Surabaya. There is a significant effects of product price, promotion, and distribution variables on the household decision in buying â€œcemment productâ€ in Surabaya. Simultaneously, motivation, attitude, refference group, product, price, premium and distribution variables, significantly affect household decision in buying â€œcemment productâ€ in Surabaya. Keywords: customer behavior, buying decision, cement.